Cyclic enzymatic repairing-mediated dual-signal amplification for real-time monitoring of thymine DNA glycosylase. Issue 27 (20th March 2017) - Wang, Li-Juan; Wang, Zi-Yue; Zhang, Qianyi; Tang, Bo; Zhang, Chun-Yang
Abstract : We develop a new fluorescence method for real-time monitoring of thymine DNA glycosylase activity through cyclic enzymatic repairing-mediated dual-signal amplification. Abstract : We develop a new fluorescence method for real-time monitoring of thymine DNA glycosylase (TDG) activity through cyclic enzymatic repairing-mediated dual-signal amplification. This method exhibits excellent sensitivity with a detection limit of 5.6 × 10 −7 U μL −1, and it can be used to determine kinetic parameters and quantify TDG activity from even single cancer cells.